1991
DOI: 10.1002/dvg.1020120503
|View full text |Cite
|
Sign up to set email alerts
|

Formation of functionally active chloroplasts is determined at a limited stage of leaf development in virescent mutants of rice

Abstract: The ability to form functionally active chloroplasts is determined at a certain early stage of leaf development in three non-allelic temperature-sensitive virescent mutants of rice. Temperature-shift analysis, together with anatomical observations, indicates that the intrinsic developmental signals of the virescent genes are expressed at the stage immediately following the formation of basic leaf structure, but just before the onset of leaf elongation. These signals control the expression of chloroplast-encode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 36 publications
5
36
0
Order By: Relevance
“…We have previously characterized three v (v1, v2, and v3) mutants in rice (Iba et al, 1991;Kusumi et al, 1997;Sugimoto et al, 2004) and recently identified the V2 gene that encodes pt/mt GK (Sugimoto et al, 2007). In this study, we have further identified the V3 and St1 genes that encode the large and small subunits of RNR, RNRL1 and RNRS1, respectively.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…We have previously characterized three v (v1, v2, and v3) mutants in rice (Iba et al, 1991;Kusumi et al, 1997;Sugimoto et al, 2004) and recently identified the V2 gene that encodes pt/mt GK (Sugimoto et al, 2007). In this study, we have further identified the V3 and St1 genes that encode the large and small subunits of RNR, RNRL1 and RNRS1, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…It has been speculated that the V1 gene product functions at the beginning of the second step of chloroplast differentiation (Kusumi et al, 1997), whereas V2 (pt/mt GK) plays a critical role in the second and third steps (Sugimoto et al, 2004(Sugimoto et al, , 2007. Plastids in the chlorotic leaves of v1 and v2 were shown to be normal in size and DNA copy number (Iba et al, 1991). However, v3 and st1 mutants exhibit a significant decrease in the size and number of their chloroplasts ( Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Why the ygl1 mutation, like ysa, dramatically affects chlorophyll biosynthesis in the early developmental stages but appears to be dispensable in the later stages is also not clear. The rice v2 mutant develops chlorotic leaves at the restrictive temperature (20°C), but develops nearly normal green leaves at the permissive temperature (30°C; Iba et al, 1991). The v2 mutation affects activation of the chloroplast translation machinery and/or expression of the plastid-to-nucleus signaling pathway during the P4 stage of leaf development (Sugimoto et al, 2004).…”
Section: Ysa Encodes a Ppr Protein Essential For Chloroplast Biogenesmentioning
confidence: 99%